RELATIONSHIPS BETWEEN SOIL SEED BANK AND VEGETATION DIVERSITY ON DIFFERENT GRAZING PRESSURE - Jargalsaikhan, Gantuya (Mongolian Journal of Agricultural Sciences, 2015)
In a case study, the main objective was to compare three sites with different grazing pressures in Hvitarsida, W-Iceland in relation to current vegetation, seed bank composition and the correlation between those. Our results show that there were significant difference in species composition in above and belowground, giving very little similarity in species composition between seed bank and current vegetation composition. The only exceptions were Agrostis capillaris and Bistorta vivipara that had close similarity between current aboveground vegetation and soil seed bank. Agrostis capillaris had a great abundance in all the sites and Bistorta vivipara proliferates mostly with bulbils that most likely were numerous in the soil. The results of our study agree with current theories on seed bank composition and similar studies,that the similarity between current above ground vegetation and soil seed bank depends on current dominant species (annual or perennial)and the productivity (high or low) of the site. Mongolian Journal of Agricultural Sciences Vol.13(2) 2014: 105-113